2018
DOI: 10.19044/esj.2018.v14n22p101
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of the Effect of Poverty on Health Care Utilization in Kenya

Abstract: Background Good health is a fundamental huma right, a valued asset, and a prerequisite for improved productivity. However, high poverty can lead to under utilization or lack of utilization of health care leading to poor health. Thus, poverty reduction and improvement of health care utilization are important in ensuring enjoyment of good health. Since 1982, poverty has remained above 40 per cent despite Kenya’s commitment to poverty reduction. Kenya’s health indicators have also not been impressive and health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
1
6
1
Order By: Relevance
“…Enrollee Income had the expected positive sign but insignificant effect on the demand for health insurance in this study, however, the positive sign implies that as income grows, the demand for health insurance would increase. The results of this study does not tally with the findings of Ajemunigbohun, Sogura and Azeez in Nigeria [36], Nanu in Ethiopia [37], Ali and Norman in Bangladesh [38] and Musyoka, Korir, Omolo and Nzai in Kenya [39] whose studies showed that income does significantly determine the demand for health insurance services. The insignificance of the variable might not be unconnected with the fact that salary levels were low, majority of the respondents in this study were in the lower income bracket, enrollees only pay 50% co-insurance for expensive investigations and 10% copayments for drugs.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Enrollee Income had the expected positive sign but insignificant effect on the demand for health insurance in this study, however, the positive sign implies that as income grows, the demand for health insurance would increase. The results of this study does not tally with the findings of Ajemunigbohun, Sogura and Azeez in Nigeria [36], Nanu in Ethiopia [37], Ali and Norman in Bangladesh [38] and Musyoka, Korir, Omolo and Nzai in Kenya [39] whose studies showed that income does significantly determine the demand for health insurance services. The insignificance of the variable might not be unconnected with the fact that salary levels were low, majority of the respondents in this study were in the lower income bracket, enrollees only pay 50% co-insurance for expensive investigations and 10% copayments for drugs.…”
Section: Discussioncontrasting
confidence: 99%
“…The distance to provider variable had a positive relationship with the demand for health insurance and it is in line with the findings of Musyoka et al in Kenya [39], Tsegay et al in Ethiopia [40] and Nanu in Ethiopia [37]. The health insurance providers in the formal sector social health insurance programme in this study offer specialized services at the reference level and hence, charge higher prices.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Poverty can suppress healthcare access through inability to afford services, low service availability, and geographic accessibility issues [16,17]. In Kenya, poverty has been associated with less healthcare utilization [18,19] and more than a third of the overall population was living below the poverty line in 2016 [20]. Additionally, the Kenyan health system is largely funded by out-of-pocket payments from patients and efforts to address the inequity arising from this structure have been mostly unsuccessful [21].…”
Section: Introductionmentioning
confidence: 99%
“…Poverty can suppress healthcare access through inability to afford services, low service availability, and geographic accessibility issues. (16,17) In Kenya, poverty has been associated with less healthcare utilization (18,19) and more than a third of the overall population was living below the poverty line in 2016. (20) Additionally, the Kenyan health system is largely funded by out-of-pocket payments from patients and efforts to address the inequity arising from this structure have been mostly unsuccessful.…”
Section: Introductionmentioning
confidence: 99%